Glutathione peroxidase 4 and vitamin E control reticulocyte maturation, stress erythropoiesis and iron homeostasis - Altamura, Sandro; Vegi, Naidu M.; Hoppe, Philipp S.; Schroeder, Timm; Aichler, Michaela; Walch, Axel; Okreglicka, Katarzyna; Hültner, Lothar; Schneider, Manuela; Ladinig, Camilla; Kuklik-Roos, Cornelia; Mysliwietz, Josef; et al. (Haematologica, 2020)
Glutathione peroxidase 4 (GPX4) is unique as it is the only enzyme that can prevent detrimental lipid peroxidation in vivo by reducing lipid peroxides to the respective alcohols thereby stabilizing oxidation products of unsaturated fatty acids. During reticulocyte maturation, lipid peroxidation mediated by 15-lipoxygenase in humans and rabbits and by 12/15-lipoxygenase (ALOX15) in mice was considered the initiating event for the elimination of mitochondria but is now known to occur through mitophagy. Yet, genetic ablation of the Alox15 gene in mice failed to provide evidence for this hypothesis. We designed a different genetic approach to tackle this open conundrum. Since either other lipoxygenases or non-enzymatic autooxidative mechanisms may compensate for the loss of Alox15, we asked whether ablation of Gpx4 in the hematopoietic system would result in the perturbation of reticulocyte maturation. Quantitative assessment of erythropoiesis indices in the blood, bone marrow (BM) and spleen of chimeric mice with Gpx4 ablated in hematopoietic cells revealed anemia with an increase in the fraction of erythroid precursor cells and reticulocytes. Additional dietary vitamin E depletion strongly aggravated the anemic phenotype. Despite strong extramedullary erythropoiesis reticulocytes failed to mature and accumulated large autophagosomes with engulfed mitochondria. Gpx4-deficiency in hematopoietic cells led to systemic hepatic iron overload and simultaneous severe iron demand in the erythroid system. Despite extremely high erythropoietin and erythroferrone levels in the plasma, hepcidin expression remained unchanged. Conclusively, perturbed reticulocyte maturation in response to Gpx4 loss in hematopoietic cells thus causes ineffective erythropoiesis, a phenotype partially masked by dietary vitamin E supplementation.
Pre-published: June 27, 2019
Gesehen am 01.04.2020